2007
DOI: 10.1038/sj.onc.1210335
|View full text |Cite
|
Sign up to set email alerts
|

Detection of novel mRNA splice variants of human ING4 tumor suppressor gene

Abstract: Inhibitor of growth (ING)4, member of a gene family encoding potential tumor suppressors, is implicated as a repressor of angiogenesis and tumor growth and suppresses loss of contact inhibition in vitro. Here, we report that ING4 undergoes alternative splicing. Expression analysis identified novel ING4 spliced variant mRNAs encoding proteins devoid of different portions. The ING4 variants were detected in both normal and tumor tissues. The existence of ING4 variants was confirmed by several approaches, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 30 publications
(73 reference statements)
2
38
0
Order By: Relevance
“…4B) show that all ING4 variants could bind to HBO1, independently of their ability to form dimers or not. This result is consistent with the previous finding that an ING4 splice variant lacking exon 2 (which codes for residues 13-37, the first two-thirds of helix ␣2) does not differ from the wild type in HBO1 binding (28). viability.…”
Section: Monomeric Ing4 Mutants Do Not Associate Inside Cells But Stillsupporting
confidence: 82%
“…4B) show that all ING4 variants could bind to HBO1, independently of their ability to form dimers or not. This result is consistent with the previous finding that an ING4 splice variant lacking exon 2 (which codes for residues 13-37, the first two-thirds of helix ␣2) does not differ from the wild type in HBO1 binding (28). viability.…”
Section: Monomeric Ing4 Mutants Do Not Associate Inside Cells But Stillsupporting
confidence: 82%
“…Subsequently, p33ING2 (ING1L), p47ING3, p29ING4 and p28ING5 were found through homology searches (Shimada et al, 1998;Nagashima et al, 2001Nagashima et al, , 2003Gunduz et al, 2002;Shiseki et al, 2003). Additionally, human ING1 and -4 transcripts can give rise to variant protein products due to alternative splicing, and some of these are regulated differently and possess functions distinct from their full-length counterparts (He et al, 2005;Unoki et al, 2006;Raho et al, 2007). All fulllength ING proteins possess a highly conserved C-terminal PHD zinc-finger characteristic of chromatin remodelling factors and a canonical nuclear localization sequence.…”
Section: Discovery Of Ing Proteinsmentioning
confidence: 99%
“…It has also been shown that the small deletion in ING4 protein leads to functional differences between the ING4 variants 25) . Moreover, alternative splicing could modulate the activity of ING4 tumor suppressor protein 26) . ING4 also has an LZL domain.…”
Section: Functional Structure Of Ing Familymentioning
confidence: 99%
“…Four different human ING4 mRNAs were generated from juxtaposed splicing sites resulting to the incorporation of 12 nucleotide coding region within a NLS domain 25,26) . It has also been shown that the small deletion in ING4 protein leads to functional differences between the ING4 variants 25) .…”
Section: Functional Structure Of Ing Familymentioning
confidence: 99%